Treatment of waste engine oil using optimized acid/clay refining method - Kamal Ariffin, Fathin Nadhirah; Ahmad Nor, Yusilawati; Sulaiman, Sarina; Jamal, Nur Ayuni (IIUM Press, International Islamic University Malaysia, 2019)
This paper addresses the treatment of waste engine oils(WEO)by acid/clay refining method using glacial acetic acid. An optimization of the process parameters in terms of settling time, stirring speed and mixing temperature for treating the WEO was performed using Response Surface Methodologyto improve the quality of treated lubricating oil.The quality of the treated WEO (Castrolbrand) was evaluated in termsof viscosity index and flash point value. The treated fuel qualityis found to have about 95% similarity to the fresh oil used as a standard at thesettling time of 24 hours, temperature of 50 °C and mixing speed of 150 rpm. Analysis of variances (ANOVA) showed that settling time plays the most significant parameters of the process followed by the mixing temperature. Solid contaminants which were collectedafterthetreatment wereanalyzed using SEM-EDS. Theycontained rough heteregenous shaped particles with elements such as carbon (97%), calcium (1.12%), zinc (0.74%), sulphur (0.73%) and phosphorus (0.29%). Then, four different brands of WEO (Liqui Moly, Castrol, Shell and Pennzoil) were treatedat the optimized conditionsto determine the feasibility of the method to treat any brandsof WEO. It can be concluded that the optimized treatement method is suitable to treat most of WEO.The findingsofthis study provide theinformation on thebest process condition for treating WEO as well as thesolid contaminants presentin it.